Sequential Blended Teaching Materials: Scaffolding Non-English Language Learners’ Scientific Literacy Using Online Sources, Edpuzzle - Bilmona, Hanafi (Pattimura Excellence Journal of Language and Culture, 2021)
This study aimed to explore information from 44 Students of Primary Teacher Training Education Department as the sample of research. The 40 items of statement in questionnaires designed from positive point of view and scaled in Likert from; strongly agree (5) to strongly disagree (1). By the content area of two basic research questions in regard to Preferences and benefit for students in applying a sequential blended learning material in teaching English. Data was analyzed in statistic descriptive to get meaning. The result found that, there was 4,22% of students respond to items of questionnaires to more agree and strongly agree to the statements of questionnaires. This total average number of the respond of 44 students were found in 4,6816 % in questionnaires that represented preferences (13 items of statements) and 3,7727% in average found in statement of questionnaires that represent benefits (27 items of statements), meant there was positive respond toward this teaching approach and fixing to the preferences of student and scaffolded students’ other related scientific literacy.